ANALISA YURIDIS ATAS KESETARAAN PARA PIHAK PADA PERJANJIAN KERJASAMA DALAM BIDANG JASA PENGAMANAN (STUDI DI PT. GARDA BHAKTI NUSANTARA) - LITA YUSTITIA LINGGA (PREMISE LAW JURNAL, 2017)
There are various innovations in cooperation agreement in society which is aimed to accommodate legal relationship which is mutually beneficial. One of them is cooperation agreement in security service. One of the companies which provides security service is PT. Garda Bhakti Nusantara, collaborating with many other companies, and one of them is PT. Ikaindo Industri Karbonik Indonesia. High activity in export of PT. Ikaindo Industri Karbonik Indonesia has made it no time to organize some types of work, and one of them is the Security department. In this case, PT. Garda Bhakti Nusantara is collaborating with PT. Ikaindo Industri Karbonik Indonesia in providing security. The problems of the research were as follows: how about the form of cooperation between PT. Garda Bhakti Nusantara as the provider of security service with companies as the users of security service, how about the equality of the parties concerned, viewed from the right and obligation in the security service contract, and how about legal consequences of the cooperation agreement between PT. Garda Bhakti Nusantara as the security service provider and the companies as the users of security service. Keywords: Cooperation Agreement, Balance, Security Service